Interrelationship of Corruption and Ecological Disaster - Muhammad Rustamaji; Bambang Santoso (Faculty of Law, Jambi University, 2019)
Human being and living quality of their global community very depends on environmental condition. Then, various policies, regulation managements, law enforcement and technical supervision are conducted in attempts of biological environment conservation. However, corruption has always been primary enemy for all aspects of the environmental conservation. Apart from all efforts that had been conducted, natural resource sector is, in fact, a fertile land for corruption. Unguaranteed property right aspect, unbalanced discretion, complexity management of natural resource product, and weakness of control are factors leading to ecological environment become vulnerable area of corruption. Ultimately, bad impacts of the environmental damage return to human being as ecological disaster on individuals as well as global people. Therefore, efforts of prevention such as to involve people in recognizing forms of corruption contributing to ecological disaster is important. Grand corruption (state capture & elite capture), middle class corruption and petty corruption are forms of corruptions of ecological environment that should be understood deeply by people.